Physical activity in mild multiple sclerosis: contribution of perceived fatigue, energy cost, and speed of walking. Issue 9 (23rd April 2020) - Kalron, Alon; Menascu, Shay; Frid, Lior; Aloni, Roy; Achiron, Anat
Abstract: Purpose: To clarify the relationship between leisure-time physical activity, perceived fatigue, and energy expenditure while walking in people with multiple sclerosis. Methods: Sixty-six people afflicted with multiple sclerosis (MS) (32 women) with a mild neurological disability, participated in this study. Energy expenditure was separately measured at rest, during comfortable walking and during fast walking via a portable metabolic device using breath-by-breath technology (COSMED K5, COSMED Srl, Rome, Italy). The Godin leisure-time exercise questionnaire assessed leisure-time physical activity. The Modified Fatigue Impact Scale determined the level of perceived fatigue. Results: Seventeen people with MS were classified as physically active; 49 were insufficiently active. Scores recorded on the Godin Leisure-Time Exercise Questionnaire were 47.8 (SD = 18.4), 7.0 (SD = 8.2), respectively. Insufficiently physically active people with MS walked slower at both normal and fast walking conditions. However, no differences between groups were observed in energy expenditure measures in both walking speeds. O2 cost was 0.20 (SD = 0.13) and 0.21 (SD = 0.06) in the active and insufficiently active group, respectively. The insufficiently active group reported more perceived fatigue compared with the active patients; 33.3 (SD = 18.6) vs. 15.0 (SD = 19.0), p value = 0.002. Perceived fatigue was a significant variable maintaining a 10.4% variance related to leisure-time physical activity. Conclusions: Leisure-time physical activity was inversely associated with perceived fatigue and walking speed in persons with mild MS. Rehabilitation professionals should be aware of these relationships when planning rehabilitation strategies. Implication for rehabilitation: This study found that perceived fatigue is a barrier to physical activity participation even in people with mild multiple sclerosis and minimal disability. Insufficiently active people with multiple sclerosis expend the same amount of energy while walking as active multiple sclerosis individuals, though walking slower. The relationship between perceived fatigue and physical activity participation requires further exploration in the multiple sclerosis population.